Observation of ground state of ⁴H in ³H(α,τt)n reaction - Gorpinich, O.K.; Povoroznyk, O.M.; Jachmenjov, O.O. (Вопросы атомной науки и техники, 2004)
In kinematical complete investigation of ³H(α,τt)n reaction by using beam with Eα = 67.2 МеV and titan trituated target the ground state of ⁴Н was observed with Eg.s. = Ent = 3.22 ± 0.25 МеV and Г = 2.9 ± 1,1 МеV.